Specific Guanosines in the HIV-2 Leader RNA are Essential for Efficient Viral Genome Packaging. Issue 2 (22nd January 2021) - Umunnakwe, Chijioke N.; Duchon, Alice; Nikolaitchik, Olga A.; Rahman, Sheikh Abdul; Liu, Yang; Chen, Jianbo; Tai, Sheldon; Pathak, Vinay K.; Hu, Wei-Shau
Graphical abstract: Highlights: Mutating specific guanosines in the HIV-2 leader RNA abrogated genome packaging. Five guanosine-containing sites were identified with varied importance to packaging. There are functional overlaps and synergistic effects among sites with guanosines. We propose that synergistic Gag:RNA interactions mediate HIV-2 RNA packaging. Abstract: HIV-2, a human pathogen that causes acquired immunodeficiency syndrome, is distinct from the more prevalent HIV-1 in several features including its evolutionary history and certain aspects of viral replication. Like other retroviruses, HIV-2 packages two copies of full-length viral RNA during virus assembly and efficient genome encapsidation is mediated by the viral protein Gag. We sought to define cis -acting elements in the HIV-2 genome that are important for the encapsidation of full-length RNA into viral particles. Based on previous studies of murine leukemia virus and HIV-1, we hypothesized that unpaired guanosines in the 5′ untranslated region (UTR) play an important role in Gag:RNA interactions leading to genome packaging. To test our hypothesis, we targeted 18 guanosines located in 9 sites within the HIV-2 5′ UTR and performed substitution analyses. We found that mutating as few as three guanosines significantly reduce RNA packaging efficiency. However, not all guanosines examined have the same effect; instead, a hierarchical order exists wherein a primary site, a secondary site, and three tertiary sites are identified. Additionally, there are functional overlaps in these sites and mutations of more than one site can act synergistically to cause genome packaging defects. These studies demonstrate the importance of specific guanosines in HIV-2 5′UTR in mediating genome packaging. Our results also demonstrate an interchangeable and hierarchical nature of guanosine-containing sites, which was not previously established, thereby revealing key insights into the replication mechanisms of HIV-2.